Jánossy elmélete az új növekedéselmélet tükrében - Tamás Tarján (Hungarian Academy of Sciences, Institute of Economics, 2010)
– If Janossy's theory should concisely be drafted, one might say that he had been researching the "real carrier of economic development" in a very original way and having formulated his theory in a specific language. He managed to identify the "carrier" of development focusing on the systematic examination of the post-war reconstruction periods, and setup a hypothesis being ascribed to his name, which allowed him to forecast - as the first and the only one in the world - the end of the post-war golden age, a decade in advance. The present study is aimed at comparing and contrasting Janossy's specifically formulated and highly genuine theories and ideas to the contemporary neo-classical economics and to the endogenous growth theory that have appeared in the nineties. The "real carrier of economic development" matches to the "human capital" of the contemporary neo-classical theory while in the endogenous growth theory it does match to the "technological progress", both appearing as separate factors of production. We present a new growth model that satisfies the best our considerations to which the a longitudinal model fitting is done for Maddison's [2003] historical data - from 1870 to present for the 19 most developed OECD countries - and for the post-war reconstruction period, as well. The same model is applied for a cross-regional analysis, after having calculated the rates of return on capital a ranking has been performed for nearly 300 (EU-27 NUTS 2) regions in the period of 2000-2005.
Keywords: O11; O18; O33; O47; N10; 330; endogenous growth theory; leader-follower model; human capital; Endogenes Wachstumsmodell; Humankapital; Technischer Fortschritt; Innovationsdiffusion; Technologietransfer; Theorie